Apakah spiritualitas berkontribusi terhadap kesehatan mental mahasiswa? - Esa Nur Wahyuni; Khairul Bariyyah (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2019)
Spirituality and mental health have become important studies in the world of education. The holistic education paradigm views the two aspects as having a very important role in determining the best development of students and their learning achievements in addition to cognitive and skill aspects. Theoretically mental health is influenced by spirituality. This study examined the effect of student spirituality on mental health in 382 new FITK Uin students Maulana Malik Ibrahim Malang. The level of mental health was measured using a mental health scale developed by Ryff and Keyes, while spirituality was measured by Religiosity and Spirituality Scale for Youth by Hernandez. The results showed the influence of spirituality on health as much as r = 0.295 and sig. amounting to 0.01. These results explain that spirituality is one of the factors that affect the level of mental health of new students